Transition from PSSP to cluster systems management (CSM) - Quintero, Dino (IBM redbooks., 2004)
This IBM Redbooks publication covers the process of converting a PSSP cluster to a CSM cluster. It examines the different tools, utilities, documentation and other resources available to help the system administrator move a system from PSSP to CSM. It also examines the different paths a customer can take to achieve this transition and illustrates these different paths with step-by-step transition scenarios of actual clustered systems. This book also makes recommendations about which procedures are most suitable for different types of customer environments (high performance technical computing, server consolidation, business intelligence, etc.) and points out the relative advantages and disadvantages of the different procedures, tools, and methods. Customers will use the working knowledge presented in this book to plan and accomplish the transition of their own clustered systems from PSSP to CSM. Are you using GPFS? This transition book covers a number of GPFS transition methods, each with its own recommendations, GPFS cluster types, advantages versus disadvantages, and step-by-step scenarios. It also shows a method of moving GPFS storage between two clusters, which could be used during hardware transition or upgrades.